STUDENTS’ PERCEPTION TOWARD THE USE OF EDMODO IN EFL CLASSROOM - Meuthia Rafa Fariha; Pipih Setiawati (English Education and Applied Linguistics Journal (EEAL Journal), 2021)
This research intended to investigate the students’ perception toward the use of Edmodo as the English quizzes medium in the EFL classroom. Qualitative research was used in this research. A case study design was applied in this research. Seven students who have used Edmodo as the English quizzes medium in one of the universities in Garut volunteered as the research participants. The data collected by using a semi-structured interview. Three participants were interviewed in a face-to-face setting, while other participants were interviewed by using WhatsApp call and WhatsApp voice notes. The data then analyzed by following Mile and Huberman’s theory that emerges from data that systematically gathered and analyzed through the research process. The steps of analyzing the data in this research were reducing the data, displaying the data, then drawing a conclusion. The result showed that students' experiences influence their perceptions. Two students who have used Edmodo for longer than the others are very understanding and can convey their opinions well. Furthermore, all participants experienced some bad things in using Edmodo, but the researcher did not found any related theory. However, the researcher did a cross-check in the Play Store in the comments section, and it was found that some Edmodo users comment on the same thing that related to this finding. Even though, all participants conveyed positive perceptions toward the use of Edmodo as the English quizzes medium.